MOIRÉ INTEFEROMETRY APPLIED TO PLANT ARCHITECTURAL STUDIES - ALBIERO, DANIEL; ATARASSI, ROBERTO T.; MACIEL, ANTONIO JOSÉ DA SILVA; DAL FABBRO, INÁCIO M.; RODRIGUES, SILVESTRE; LINO, ANTONIO C. L. (Revista Brasileira de Engenharia de Biossistemas, 2008)
Plant architecture research subjects are of significant importance to genetics, photosynthesis, transpiration, crop-machine mechanical relationship, etc. In this sense, this research work had been carried in developing a new technique to generate the three dimensional view of plant shape. In this work the plant architecture determination will be carried out by means of a phase shift moiré method. The importance of the proposed method is based on the application of a sequence of four grids out of phase by an angle of Ï€/2 radians one from each other. A digital camera was employed to capture the moiré patterns, which will generate the image to be processed. The procedure of image analysis involved softwares as Microsoft Powerpoint, Coreldraw and Idrisi. The use of a highly continuous sinusoidal grid, of a collimated light beam, of a higher resolution Charge Coupled Device Camera, as well as the superposition of image discontinuities during the unwrapping procedure included in the phase shifting method, avoided noise occurrence satisfactorily, improving image quality.The conception of tests leading to height determination to generate a topographic description of a plant model was conceived based on optical moiré techniques. Obtained results reveal a great potential of the proposed method in determining plant architecture with high precision, at low cost and being not time demanding.